2017
DOI: 10.1001/jamapsychiatry.2017.0429
|View full text |Cite
|
Sign up to set email alerts
|

Brief Behavioral Therapy for Pediatric Anxiety and Depression in Primary Care

Abstract: clinicaltrials.gov Identifier: NCT01147614.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 49 publications
(84 reference statements)
2
69
0
Order By: Relevance
“…The 19 relevant studies included 12 case studies/case series [ 45 – 56 ], three uncontrolled pre–post designs [ 57 – 59 ], and four RCTs [ 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 19 relevant studies included 12 case studies/case series [ 45 – 56 ], three uncontrolled pre–post designs [ 57 – 59 ], and four RCTs [ 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…All three papers were consulted for novel details for data extraction. Weersing and colleagues reported their RCT in two publications [ 37 , 63 ]: data from 2017 were extracted only as these covered details from the 2016 publication. The data reported across from individuals in the case studies by Pass and colleagues [ 54 – 56 ] are also included in the pre/post study [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample consisted of mostly non-Latino White (69%) adolescents. Most recently, Weersing et al (2017) conducted a study of brief behavior therapy (BBT) compared to assisted referral to outpatient care for youth anxiety and depression treatment in primary care settings. They found that BBT was superior to assisted referral for treatment outcomes for anxiety and particularly for Hispanic youth.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also supports the efficacy of more intensive interventions for emotional and behavioral problems among pediatric patients in primary care [68•], suggesting that high-quality behavioral health services can be provided in this setting. Weersing and colleagues [72] found support for a brief behavior therapy intervention for youth anxiety and depressive disorders. Children and adolescents who participated in treatment exhibited greater and faster depression and anxiety symptom reduction and functional improvements than those referred for outpatient care.…”
Section: Special Considerations For Treating Depression In the Pcmh: mentioning
confidence: 99%